2018
DOI: 10.3390/ijms19071834
|View full text |Cite
|
Sign up to set email alerts
|

A Synergistic Anti-Cancer Effect of Troglitazone and Lovastatin in a Human Anaplastic Thyroid Cancer Cell Line and in a Mouse Xenograft Model

Abstract: Anaplastic thyroid cancer (ATC) is a malignant subtype of thyroid cancers and its mechanism of development remains inconclusive. Importantly, there is no effective strategy for treatment since ATC is not responsive to conventional therapies, including radioactive iodine therapy and thyroid-stimulating hormone suppression. Here, we report that a combinational approach consisting of drugs designed for targeting lipid metabolism, lovastatin (an inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A reductase, HMGCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…We confirmed that the growth-inhibitory effect of statins in OSCC cells is associated with the suppression of cell cycle progression. Similar to our results, statins have been reported to arrest cancer cells such as G 0 /G 1 phase arrest in glioma, hypopharyngeal cancer [ 9 ], anaplastic thyroid cancer [ 10 ], liver cancer [ 11 ], and bladder cancer [ 12 ]; G 1 phase in HeLa cells [ 13 ], anaplastic thyroid cancer [ 14 ], and nasopharyngeal [ 15 ]; G 1 S in hepatocellular carcinoma [ 16 ] and colon cancer [ 17 ]; and S phase in prostate cancer [ 18 ]. Moreover, statins upregulated the p21 mRNA and protein expression and downregulated the expression of CDK2, CDK4, and CDK6 in OSCC cells.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We confirmed that the growth-inhibitory effect of statins in OSCC cells is associated with the suppression of cell cycle progression. Similar to our results, statins have been reported to arrest cancer cells such as G 0 /G 1 phase arrest in glioma, hypopharyngeal cancer [ 9 ], anaplastic thyroid cancer [ 10 ], liver cancer [ 11 ], and bladder cancer [ 12 ]; G 1 phase in HeLa cells [ 13 ], anaplastic thyroid cancer [ 14 ], and nasopharyngeal [ 15 ]; G 1 S in hepatocellular carcinoma [ 16 ] and colon cancer [ 17 ]; and S phase in prostate cancer [ 18 ]. Moreover, statins upregulated the p21 mRNA and protein expression and downregulated the expression of CDK2, CDK4, and CDK6 in OSCC cells.…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that the functions of kinases have been inhibited by p21 upregulation. Similar to our results, statins have been reported to upregulate p21 expression in glioma, hypopharyngeal cancer [ 9 ], anaplastic thyroid cancer [ 10 , 14 ], liver cancer [ 11 ], HeLa cells [ 13 ], colon cancer [ 17 ], oral cancer [ 29 ], and melanoma [ 30 ]. p21 also negatively regulates the cell cycle by binding to proliferating cell nuclear antigen (PCNA) through its carboxyl-terminal domain, thus blocking DNA replication [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several agents have been identified to inhibit the expression of Skp2 in human cancer. For example, troglitazone, an agonist of peroxisome proliferator-activated receptor gamma, was identified to downregulate the expression levels of Skp2 and to induce p27-associated cell cycle arrest in liver cancer cells (33,34). EB1089 induced Skp2-dependent p27 accumulation, resulting in inhibition of cell growth and cell cycle G1 phase arrest in hepatoma cells (35).…”
Section: Discussionmentioning
confidence: 99%